MnFtz-f1 Is Required for Molting and Ovulation of the Oriental River Prawn Macrobrachium nipponense - Yuan, Huwei; Zhang, Wenyi; Fu, Yin; Jiang, Sufei; Xiong, Yiwei; Zhai, Shuhua; Gong, Yongsheng; Qiao, Hui; Fu, Hongtuo; Wu, Yan (Frontiers in Endocrinology, 2021)
Molting and ovulation are the basic processes responsible for the growth and reproduction of Macrobrachium nipponense; however, the molecular mechanisms of molting and ovulation in M. nipponense are poorly understood. The present study aimed to use MnFtz-f1 as the starting point to study the molting and ovulation phenomena in M. nipponense at the molecular level. The full-length MnFtz-f1 cDNA sequence was 2,198 base pairs (bp) in length with an open reading frame of 1,899 bp encoding 632 amino acids. Quantitative real-time PCR analysis showed that MnFtz-f1 was highly expressed in the ovary at the cleavage stage and on the fifth day after hatching. In vivo administration of 20-hydroxyecdysone (20E) showed that 20E effectively inhibited the expression of the MnFtz-f1 gene, and the silencing of the MnFtz-f1 gene reduced the content of 20E in the ovary. In situ hybridization (ISH) analysis revealed the localization of MnFtz-f1 in the ovary. Silencing of MnFtz-f1 by RNA interference (RNAi) resulted in significant inhibition of the expression of the vitellogenin (Vg), Spook, and Phantom genes, thus confirming that MnFtz-f1 had a mutual regulatory relationship with Vg, Spook, and Phantom. After RNAi, the molting frequency and ovulation number of M. nipponense decreased significantly, which demonstrated that MnFtz-f1 played a pivotal role in the process of molting and ovulation.